Assessment of Electronic and Electric Waste Pollution Case Study: Kigali City – Rwanda - Christophe Nsanzamahoro; Fuad Muhammad; M. Maryono (Journal of Bioresources and Environmental Sciences, 2023)
The issue of electronic goods and the pollution they generate is a rapidly growing global concern. These are regarded as any appliances using an electric power supply that has reached their end-of-life. They contain various components, some of which contain harmful substances that cause risks to both human health and the environment. Due to rapid economic growth, urbanization, and increased consumer demand, the manufacturing and usage of electronic devices have a significant increase on the annual growth rate of 5% to 8% compared to other solid wastes. It is in this context that this research aims to assess the awareness and knowledge levels of e-waste pollution, as well as the handling practices and attitudes towards e-waste among residents of Kigali City, Rwanda. The study took place in three districts of Kigali City: Gasabo, Nyarugenge, and Kicukiro, where data were collected using a questionnaire survey administered to a sample of respondents (n=204) living in the city of Kigali. Statistical data analysis was applied on the analysis of the collected information determining the significancy. The results indicated a limited awareness of e-waste pollution among electronic users and identified significant health risks faced by workers and repairers of electronic devices. Thus, a low level of knowledge, noticeable prevalence of inadequate e-waste pollution practices and absence of regulations and legislation concerning e-waste and recycling activities was also identified as a problem. Therefore, educating individuals, raising awareness, and promoting environmental concern implementing the three "Rs", reduce, reuse, and recycle to maximize re-source efficiency and material utilization needs to be enhanced.